How Do Regional Interactions in Space Affect China's Mitigation Targets and Economic Development? - Wang Lu; Hao Yu; Wei Yi-Ming (Fondazione Eni Enrico Mattei (FEEM), 2017)
China is faced with the big challenge of maintaining a remarkable economic growth in an environmental friendly manner; that is why forecasting the turning point is of necessity. Traditional econometric approaches do not consider the spatial dependence that inevitably exists in the economic units, which probably risks misspecification and generating a biased estimation result. This paper firstly constructs Theil index to measure the intra-and inter regional inequality of CO2 emissions, we find that difference in emissions between regions is narrowed but gap within the Western China is sharply expanding. Then the Spatial Durbin model is employed to shape the relationship between mitigation and economic growth using the panel data of 29 provinces ranging from 1995 to 2011. Results show that the peak of per capita carbon dioxide emissions in China would be seen when GDP per capita reaches between USD 21594 to 24737 (at 2000 constant price), much smaller when compared with the estimations of models which ignore the spatial dependence. This implies that territorial policy and industry transfer, on one hand would favor those underdeveloped regions with investment, technology and labors transfer; on the other hand enables developed regions more potential to mitigation, thus, chances are that China achieves the emissions peak of carbon dioxide earlier than conventional wisdom.
Keywords: C31; P48; Q54; 330; Mitigation; Economic growth; Spatial Interaction; Spatial Durbin Model